Application of Path Analysis on Incidence of Anemia in Female Adolescents - Handayani, Dwi; Pamungkasari, Eti Poncorini; Sulaeman, Endang Sutisna (Jurnal Gizi dan Pangan, 2019)
The aim of the study was to analyse the direct and indirect effects of knowledge, attitudes, and eating behavior on anthropometry status and anemia incidence in female adolescents. This observational study employed case-control design and involved a total with total of female adolescents 117, classified into case groups (n=39) and control groups (n=78). The data were collected using questionnaires on knowledge and attitude about nutrition of anemia and eating behaviors, 2x24 hour food recall, Food Frequency Questionnaire (FFQ), anthropometry, and also Hb level measurement by Cyanmethemoglobin method. The data were analysed using path analysis. The results showed that there was a significant relationship (p<0.05) and direct effects between eating behavior on anthropometry status and incidence of anemia, which accounted for 66% and 22% respectively. There was no relationship (p>0.05) and indirect effects between attitude and incidence of anemia with value 4.1%. Eating behavior had a strong effect on anemia incidence through anthopometry in female adolescents.